Caracterização físico socioambiental e enquadramento de áreas verdes urbanas de Votorantim-SP - Gerdenits, Daniela (2013)
Within the process of urbanization green areas emerge as alternatives contemplating new cultural and aesthetic aspects, which come to extrapolate their functions and uses. This work fits within the proposed Master Plan Votorantim, and aims to identify, characterize, and assign frame through proposals, significant urban green areas of the city. These were characterized by a physical diagnosis through environmental field trips, maps present in the Secretariat of works pertaining to their subdivisions and public areas, information contained in the Master Plan and georeferenced images. Among the twelve areas, nine can be considered neighborhood parks and only three as neighborhood parks, mainly due to its dimensions. Regarding the state of conservation of the environment is worth highlighting three green areas, while the other studied have a higher degree of intervention, mostly with furniture and spaces waterproofed. Others are in a high degree of degradation, mainly by the accumulation of garbage. The enhancement and protection of green areas should be priorities in any master plan, based on the development of projects that include management programs, requiring detailed planning for these areas do not become problems for the city, eventually being abandoned or illegally occupied.